2002
DOI: 10.1152/ajplung.00085.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-stimulated lung epithelial Na+transport is associated with regulated ENaC andsgk1expression

Abstract: H441 cells, a bronchiolar epithelial cell line, develop a glucocorticoid-regulated amiloride-sensitive Na(+) transport pathway on permeable supports (R. Sayegh, S. D. Auerbach, X. Li, R. Loftus, R. Husted, J. B. Stokes, and C. P. Thomas. J Biol Chem 274: 12431-12437, 1999). To understand its molecular basis, we examined the effect of glucocorticoids (GC) on epithelial Na(+) channel (ENaC)-alpha, -beta, and -gamma and sgk1 expression and determined the biophysical properties of Na(+) channels in these cells. GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
126
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 61 publications
14
126
1
Order By: Relevance
“…Indeed, glucocorticosteroids have been shown to induce a-ENaC transcription, 57,58 and in human fetal lung explant cultures all three ENaC subunits were upregulated by glucocorticosteroids. 59,60 Glucocorticosteroids also increase the number of available sodium channels by increasing ENaC trafficking and decreasing the rate of degradation of existing channels 61,62 and improving lung responsiveness to b2 stimulants and thyroid hormones. 63 Stutchfield et al 64 have shown that two doses of betamethasone given 48 h before cesarean section significantly decreased admissions due to respiratory distress.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…Indeed, glucocorticosteroids have been shown to induce a-ENaC transcription, 57,58 and in human fetal lung explant cultures all three ENaC subunits were upregulated by glucocorticosteroids. 59,60 Glucocorticosteroids also increase the number of available sodium channels by increasing ENaC trafficking and decreasing the rate of degradation of existing channels 61,62 and improving lung responsiveness to b2 stimulants and thyroid hormones. 63 Stutchfield et al 64 have shown that two doses of betamethasone given 48 h before cesarean section significantly decreased admissions due to respiratory distress.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…On the other hand, GILZ stimulated rather than suppressed the expression and activity of the epithelial sodium channel α (ENaCα) (Bhalla et al, 2006;Soundararajan et al, 2005), possibly via inhibition of the ERK pathway (Ayroldi et al, 2002;Soundararajan et al, 2005). ENaCα expression is thought to contribute to GC-induced hypertension (Fuller et al, 2000;Itani et al, 2002;Sayegh et al, 1999;Stokes and Sigmund, 1998). This raises the interesting possibility that a GCinduced gene could contribute to both anti-inflammatory and harmful effects in a single cell type.…”
Section: A Clarkmentioning
confidence: 99%
“…The Clara-like H441 lung papillary adenocarcinoma cell line has been used as a glucocorticoid-and cAMP-regulated cellular model of pulmonary epithelial sodium absorption (5)(6)(7)(8)(9)(10). These cells produce the Clara cell 10-kDa protein (CC-10) and the surfactant proteins A, B, and D and have ultrastructural characteristics of nonciliated bronchiolar cells (11).…”
mentioning
confidence: 99%